2000
DOI: 10.1111/0033-0124.00209
|View full text |Cite
|
Sign up to set email alerts
|

Changing Intra-Urban Location Patterns of Major League Sports Facilities

Abstract: The boom in U.S. major league sporting venue construction has forced many cities to face issues related to the provision of such facilities, including the location choice. Recent data show that the suburbanization trend long assumed in the literature has been reversed, with a resurgence in downtown venues. This paper demonstrates the reversal and discusses the reasons behind this recent trend. These include a concomitant trend toward smaller market franchises, increasing corporate sponsorship, deliberate downt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Other amenities which add to a significantly larger facility footprint than Jewel Box era venues (9.42 acres) presented by Seifried and Pastore (2009b) include an on-site retail store, restaurants, and interactive entertainment zones. Overall, we found evidence that the present era of MLB facilities followed the blueprint laid out by Oriole Park and that this notion is supported by Chapin (2000Chapin ( , 2004 and Newsome and Comer (2000).…”
Section: Major League Baseballsupporting
confidence: 64%
“…Other amenities which add to a significantly larger facility footprint than Jewel Box era venues (9.42 acres) presented by Seifried and Pastore (2009b) include an on-site retail store, restaurants, and interactive entertainment zones. Overall, we found evidence that the present era of MLB facilities followed the blueprint laid out by Oriole Park and that this notion is supported by Chapin (2000Chapin ( , 2004 and Newsome and Comer (2000).…”
Section: Major League Baseballsupporting
confidence: 64%
“…With few exceptions, little attention has been given to where they play within the metropolitan area. Newsom and Comer (2000) observe a shift in new stadiums location from the suburbs and central cities and downtowns, but they did not assess economic outcomes. Nelson (2001) observed general outcomes based on location but did not assess individual markets.…”
Section: Literature Review and Research Issuesmentioning
confidence: 99%
“…These urban stadium locations may be prime downtown or waterfront property or inner city areas in need of economic revitalization. Newsome and Comer (2000) found that the suburbanization trend in stadium construction characteristic of the period from 1965 to 1985 had been reversed by 1997, exhibiting "a downtown resurgence" that the authors found to be statistically significant. 3 Owners have sought to play in stadiums and arenas designed to generate higher profits.…”
Section: Chapter II Historical Contextmentioning
confidence: 93%
“…Totaling more than $20 billion in construction costs (Baade, 2003), professional sports stadiums and arenas over the last 30 years have been in the midst of what many have termed a "construction boom" (Coates and Humphreys, 2003;Kennedy and Rosentraub, 2000;Newsome and Comer, 2000). By 2002, more than 61 percent of the 121 professional sports franchises were playing their home games in a facility built since 1991 (Kennedy and Rosentraub, 2000, p. 436).…”
Section: Chapter II Historical Contextmentioning
confidence: 99%
See 1 more Smart Citation